Clinical impact of advanced chronic kidney disease on outcomes and in-hospital complications of Takotsubo Syndrome (broken-heart-syndrome): Propensity-matched national study. (15th February 2019) - Yassin, Ahmed S.; Adegbala, Oluwole; Subahi, Ahmed; Abubakar, Hossam; Akintoye, Emmanuel; Abdelrahamn, Mohamed; Ahmed, Abdelrahman; Agarwal, Anika; Shokr, Mohamed; Pahuja, Mohit; Elder, Mahir; Kaki, Amir; et al.
Abstract: Multiple studies evaluated the outcomes and complications rate of Takotsubo Syndrome (TTS) in patients with and without advanced chronic kidney disease (CKD), revealed conflicting results. This study aims to assess the clinical outcomes and impact of advanced CKD on patients hospitalized with Takotsubo Syndrome. Patients who presented with Takotsubo cardiomyopathy between 2010 and 2014 were identified in the National Inpatient Sample (NIS) database using the International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9-CM), and subsequently were divided into two groups, with advanced CKD and without advanced CKD. NIS is the largest all-payer inpatient stays database in the United States. The primary outcome was the effect of advanced CKD on inpatient mortality in comparison to the non-advanced CKD group. Secondary outcomes were the impact of CKD on TTS in-hospital complications. We also evaluated the length of hospital stay and the cost of hospitalization. Propensity score-matched analysis was performed to address potential confounding. The advanced CKD group had no significant increase in the risk of In-hospital mortality (OR 0.99; 95% CI 0.75–1.31, P = 0.269). However, advanced CKD patients were more likely to develop acute kidney injury (AKI) requiring dialysis (OR: 5.12, 95% CI: 3.16–8.30, P = < 0.0001), and were more likely to stay longer at the hospital (OR 1.12; 95% CI 1.03 to 1.22, P 0.010). In conclusion, advanced chronic kidney disease does not increase immediate in-hospital mortality, neither most of the TTS in-hospital complications, apart from AKI and hospital length of stay, in comparison to the patients with non-advanced CKD. Highlights: The study aims to assess impact of advanced CKD on clinical outcomes of patients hospitalized with Takotsubo Syndrome (TTS). Study population included 24, 595 patients from national inpatient sample registry (NIS). All patients hospitalized for Takotsubo Cardiomyopathy in 2010-2014. Propensity score analysis performed to treat confounders. The primary outcome was the effect of advanced CKD on inpatient mortality in comparison to the non-advanced CKD group. Secondary outcomes were impact of CKD on TTS in-hospital complications, length of stay and the cost of hospitalization. Advanced CKD group had no significant increase in the risk of In-hospital mortality. Advanced CKD group is more likely to develop acute kidney injury requiring dialysis & likely to stay longer at the hospital. Advanced CKD is a predictor of increased renal complications in patients presenting with TTS.